FACTORS RELATED TO BURDEN AND SELF-CARE FOR HYPERTENSION IN FAMILY CAREGIVERS - Lima, Talita Morais Ferreira; Costa, Andréa Fachini da; Lopes, Maria Carolina Barbosa Teixeira; Campanharo, Cássia Regina Vancini; Batista, Ruth Ester Assayag; Fernandes, Hugo; Okuno, Meiry Fernanda Pinto (Cogitare Enfermagem, 2023)
Objective: To identify factors related to burden and self-care for hypertension in family caregivers. Method: an online, cross-sectional survey of 68 family caregivers of elderly people, carried out between December 2021 and February 2022 in Brazil. Questionnaires on caregiver activity, the Informal Caregiver Burden Assessment Questionnaire and the Hypertension Self-Care Scale were applied. Descriptive and analytical analyses were carried out. Results: caregivers who lived with the elderly (p=0.0006) and had no rest day (p=0.0097) showed greater burden. The longer the time as a caregiver (p=0.0411), the lower the score in the domain of self-care management measures during blood pressure decompensation. Caregivers who received help from someone else (p=0.0379) had a higher score in the domain of the patient’s degree of confidence in self-care related to hypertension. Conclusion: This study contributes to a better understanding of the variables relating to caregiver activity related to burden and self-care for hypertension among caregivers of elderly people.